Jeden, by wszystkimi rządzić Świat transmedialny (transmedial world) a uniwersum Wiedźmina - Maj, Krzysztof M (Śląskie Studia Polonistyczne, 2017)
The article makes use of Lisbeth Klastrup and Susana Tosca’s notion of transmedial world which has not been introduced to Polish humanities so far. The notion serves here to describe the characteristics of the Witcher universe encompassing books, movies, TV series, video games trilogy, role-playing games and comics. The analysis of the Witcher’s world is also the point of departure for a comparative study between the way the transmedial world is constructed and transmedial story as described in Henry Jenkins’s Convergence Culture. Additionally, it enables the author to comment upon the narrative dynamics of fantasy worldbuilding which differs considerably from traditional mechanisms of representation.